2006
DOI: 10.2353/ajpath.2006.060196
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor-β Receptor Activation Is Essential for Fibroblast and Pericyte Recruitment during Cutaneous Wound Healing

Abstract: Connective tissue remodeling provides mammals with a rapid mechanism to repair wounds after injury. Inappropriate activation of this reparative process leads to scarring and fibrosis. Here, we studied the effects of platelet-derived growth factor receptor-␤ blockade in vivo using the platelet-derived growth factor receptor (PDGFR)-␤ inhibitor imatinib mesylate on tissue repair. After 7 days, healing of wounds was delayed with significantly reduced wound closure and concomitant reduction in myofibroblast freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
130
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 43 publications
(49 reference statements)
4
130
1
1
Order By: Relevance
“…PDGF secretion has been implicated as an autocrine growth factor for myofibroblasts in vitro, but its role in vivo in the initiation and progression of fibrosis in the kidney is less clear, 37 although in skin wound-healing, PDGFR␤ blockade has been reported to delay wound closure. 38 Macrophages are necessary for proliferation of kidney fibroblasts and induction of matrix deposition. 39 Future studies should determine whether macrophage delivered PDGF is important in the initiation of fibrosis and pericyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF secretion has been implicated as an autocrine growth factor for myofibroblasts in vitro, but its role in vivo in the initiation and progression of fibrosis in the kidney is less clear, 37 although in skin wound-healing, PDGFR␤ blockade has been reported to delay wound closure. 38 Macrophages are necessary for proliferation of kidney fibroblasts and induction of matrix deposition. 39 Future studies should determine whether macrophage delivered PDGF is important in the initiation of fibrosis and pericyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism for this, as mentioned above, is through the PDGF/PDGFRβ axis. Signaling through this pathway results in a potent chemotactic and mitogenic response seen in pericyte recruitment, both during development 69, 70, and following tissue injury 71, 72. In cell culture, it has been reported that amniotic epithelial cells produce PDGF‐B 73, 74, and therefore, could potentially serve as a stimulus for perivascular migration in vivo.…”
Section: Are Wharton's Jelly Mscs Perivascular In Origin?mentioning
confidence: 99%
“…PDGF receptor b (PDGFRb) signaling is essential for angiogenesis and for recruitment, proliferation, and normal function of fibroblasts and pericytes during the tissue-formation phase. 3 Blockade of VEGF receptor signaling and PDGFRb signaling inhibits angiogenesis and results in delayed wound healing, 3,4 indicating that angiogenesis is critical for normal wound healing.…”
mentioning
confidence: 99%